Molecular Analysis of an Intestinal Neuroendocrine/Non-neuroendocrine Neoplasm (MiNEN) Reveals MLH1 Methylation-driven Microsatellite Instability and a Monoclonal Origin: Diagnostic and Clinical Implications. Issue 2 (February 2022) - Sciammarella, Concetta; Bencivenga, Maria; Mafficini, Andrea; Piredda, Maria L.; Tsvetkova, Vassilena; Paolino, Gaetano; Mastrosimini, Maria G.; Hetoja, Selma; de Manzoni, Giovanni; Mattiolo, Paola; Borga, Chiara; Fassan, Matteo; et al.
Abstract : Mixed neuroendocrine/non-neuroendocrine neoplasms (MiNEN) are rare mixed epithelial neoplasms in which a neuroendocrine component is combined with a non-neuroendocrine component. Here, we provide the clinical, pathologic, and molecular report of a 73-year-old-man presenting with an intestinal MiNEN. The lesion was composed of a well-differentiated G3 neuroendocrine tumor and a colloid adenocarcinoma. The molecular characterization was performed using a multigene next-generation sequencing panel. The neoplasm displayed microsatellite instability due to MLH1 promoter methylation. The extended molecular profile documented the same mutations affecting ARID1A, ASXL1, BLM, and RNF43 genes in both components, indicating a monoclonal origin of the tumor. Regarding component-specific gene mutations, BRCA2 was specifically altered in the neuroendocrine area. It may represent a new actionable target for precision oncology in MiNEN, but the lack of its alteration in the colloid component calls for further considerations on intratumor heterogeneity. The most important finding with potential immediate implications regards the presence of microsatellite instability: it indicates that this molecular alteration should become part of the diagnostic algorithm for these rare neoplasms.